Bukhara from the history of the events of the organization of the air fleet of modern new technology and the introduction of aircraft - Elova, Dilnoza; Ahmadov, Olimjon (E3S web of conferences, 2024)
In 1920-1924, the activities carried out in Bukhara regarding the establishment of the air fleet and the establishment of airplane traffic were covered through the analysis of primary sources and literature. The discovery of airplanes as a means of transport and the beginning of their use is related to the history of countries in Europe such as France and Germany. In 1924, a total of 1,000 passengers, 200 kg of mail, and 5 tons of cargo were transported by air in our country. The history of the establishment of the air fleet and the arrival of the first airplanes in Turkestan dates back to the first decade of the 20th century. On March 28-29, 1912, the pilot Sedov flew over Tashkent in his plane, and on March 29, 4 women and 3 men flew over Tashkent. The guests who visited Tashkent also flew in an airplane and watched the city view from above. The article serves to improve state programs aimed at creating a new generation of history textbooks and training manuals, writing fundamental works, organizing special courses, and implementing socio-economic and cultural innovations.